Manajemen Kesiswaan dalam Meningkatkan Mutu Pembelajaran di SMK Negeri Muara Beliti - Satria, Fitra; Agussalim, Agussalim; Purna Irawan; Supriadi, Supriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the implementation of student management in improving the quality of learning at SMK Negeri Muara Beliti. Student management is viewed as a strategic aspect that plays a crucial role in developing students' character, discipline, and motivation to learn. This study used a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation involving the principal, guidance and counseling teachers, subject teachers, and active students. The results indicate that the student organization structure at SMK Negeri Muara Beliti is well-organized and involves all teachers in program implementation. Character development activities, the Student Council (OSIS), and extracurricular activities contribute positively to improving student discipline and enthusiasm for learning. Key supporting factors include collaboration between teachers and a personal approach to students, while challenges include limited human resources and concurrent positions. Overall, student management has been shown to have a significant influence on improving the quality of learning through the development of student character, motivation, and academic achievement. The results of this study are expected to serve as a reference for other vocational schools in developing effective and sustainable student management strategies. Keywords: Student Management, Learning Quality, Character Building, Student Discipline